Challenges of Pediatric Cataract Surgery in a Case of Seasonal Hyperacute Panuveitis (SHAPU). (28th August 2021) - Karki, Pratap; Sitaula, Ranju Kharel; Khatri, Anadi; Joshi, Sagun Narayan; Gurung, Haramaya; Maharjan, Indraman; Sharma, Ananda Kumar; Upadhaya, Madan Prasad
Abstract : A four-year-old female child diagnosed as a case of severe Seasonal Hyperacute Panuveitis (SHAPU) underwent lens-sparing core vitrectomy in her left eye with intravitreal antibiotic and steroid. Patient responded well to treatment and intraocular inflammation subsided. However, three months later, she developed vision impairing dense cataract which also made posterior segment assessment difficult. Lens aspiration with primary posterior capsulotomy and anterior vitrectomy with intraocular lens (IOL) implantation was performed. However, four weeks later, the patient developed occlusio pupillae with iris bombe. She did not respond to medical management so synechiolysis with surgical iridectomy was performed after which a normal depth anterior chamber was attained. Synechia and iris bombe were also relieved, and vision was regained.